Pressurized metered-dose inhalers using next-generation propellant HFO-1234ze(E) deposit negligible amounts of trifluoracetic acid in the environment - Tewari, Shivendra G.; Bell, John P.; Budgen, Nigel; Platz, Stefan; Gibbs, Megan; Newham, Peter; Kimko, Holly (Frontiers in Environmental Science, 2023)
Pressurized metered-dose inhalers (pMDIs) deliver life-saving medications to patients with respiratory conditions and are the most used inhaler delivery device globally. pMDIs utilize a hydrofluoroalkane (HFA), also known as an F-gas, as a propellant to facilitate the delivery of medication into the lungs. Although HFAs have minimal impact on ozone depletion, their global warming potential (GWP) is more than 1,000 times higher than CO2, bringing them in scope of the F-Gas Regulation in the European Union (EU). The pharmaceutical industry is developing solutions, including a near-zero GWP “next-generation propellant,” HFO-1234ze(E). At the same time, the EU is also evaluating a restriction on per-and polyfluoroalkyl substances (PFAS) under the Registration, Evaluation, Authorization, and Restriction of Chemicals (REACH) regulation. Trifluoroacetic acid (TFA) is a persistent PFAS and a potential degradation product of HFO-1234ze(E). We quantified yield of TFA from HFO-1234ze(E) using a computational model under Europe-relevant atmospheric conditions. The modeling suggests that most HFO-1234ze(E) degrades into formyl fluoride within 20 days (≥85%) even at the highest examined altitude. These results suggest that TFA yield from HFO-1234ze(E) varies between 0%–4% under different atmospheric conditions. In 2022, France represented the highest numbers of pMDI units sold within the EU, assuming these pMDIs had HFO-1234ze(E) as propellant, we estimate an annual rainwater TFA deposition of ∼0.025 μg/L. These results demonstrate negligible formation of TFA as a degradation product of HFO-1234ze(E), further supporting its suitability as a non-persistent, non-bioaccumulative, and non-toxic future propellant for pMDI devices to safeguard access for patients to these essential medicines.